Analisi Kepastian Hukum Terhadap Putusan Nikah Beda Agama Pada Penetapan Pengadilan Negeri Pontianak Nomor 12/Pdt.P/2022/PN.Ptk Pengadilan Negeri Blora Nomor 71/Pdt.P/2017/PN.Bla - Ahmad Nuril Madani; Bashori Alwi (CV. Ulil Albab Corp, 2026)
Abstract: : Indonesia is a unitary state consisting of thousands of large and small islands, and it is made up of various ethnic groups, cultures, and religions, with the motto Bhinneka Tunggal Ika. Interaction between ethnic groups, races, and religions is the initial gateway for people to get to know each other, and from these interactions, some progress to the stage of marriage, and there are even instances of marriages taking place despite differences in religion. Over time, this is feared to potentially cause problems if referring to the norms within religions regarding certain boundaries in marriage. This led to a decision by the District Court Number 12/Pdt.P/2022/PN.Ptk., which granted a request for the registration of an interfaith marriage. The ruling certainly attracted attention in Pontianak, considering it would be carried out according to the laws of each respective religion. Even though the registration has been regulated in Article 35 Letter (a) of Law Number 23 of 2006 Law Number 24 of 2013 on Population Administration, yet the regulation regarding interfaith marriage in the Marriage Law still experiences a legal vacuum. It is hoped that this writing can provide the public with insights into the issues surrounding the implementation of interfaith marriage in Indonesia.